STUDYING WORKS ON HISTORICAL TOPICS IN STUDY LESSONS - Amirkulova Zebuniso Mustafakulovna, Kurbanova Saltanat Nurmuhammedovna (American Journals, 2023)
In this article, the methodology of studying historical works in reading classes is studied, and information is given about the innovative technologies used in the course of the lesson.